Effects of Matched Intermittent and Continuous Exercise on Changes of Cardiac Biomarkers in Endurance Runners - Li, Feifei; Nie, Jinlei; Zhang, Haifeng; Fu, Frank; Yi, Longyan; Hopkins, Will; Liu, Yang; Lu, Yifan (Frontiers in Physiology, 2020)
Purpose: Endurance runners training with high-intensity intermittent exercise might experience damage to cardiac muscle. We have therefore compared changes of cardiac biomarkers after workload-matched intermittent and continuous exercise. Methods: Twelve endurance runners (11 males, 1 female; means ± SD VO2max, 62.4 ± 5.4 ml.kg−1.min−1; velocity of VO2max [vVO2max], 17.1 ± 1.4 km.h−1) completed an intermittent and continuous exercise trial in random order. Intermittent exercise consisted of running at 90% vVO2max for 2 min followed by 50% vVO2max for 2 min, repeated for 92 min. Continuous exercise was performed at 70% vVO2max for 92 min. Blood samples were drawn before and 0, 2, 4, 24 and 48 h after exercise for assay of various cardiac biomarkers. Changes in concentration of biomarkers were averaged for the comparison of intermittent with continuous exercise after adjustment for baseline concentration and exercise intensity expressed as percent of heart-rate reserve (%HRR); magnitudes were assessed by standardization. Results: There were moderate and large increases in high-sensitivity cardiac troponin-I and -T respectively following exercise. The differences between the increases adjusted to the mean intensity of 78 %HRR were trivial, but at 85 %HRR the increases for cardiac troponin-I and -T were moderately higher for intermittent compared with continuous exercise (factor difference, 90% confidence limits: 3.4, 1.9 and 2.1, 1.8 respectively). Differences in the changes in other cardiac biomarkers were trivial. Conclusion: Prolonged intermittent exercise is potentially more damaging to cardiac muscle than continuous exercise of the same average running speed at higher average heart rates in endurance runners.